Depression and associated factors in adolescents from a school in the city of Huanuco, Peru - Bustillos-Cotrado, Anthony (2018)
Introduction: The objective of the present study was to determine the relationship between depression and three associated factors (family dysfunction, distorted body image and bullying) in adolescents from a school of Huánuco City in Peru, October 2016. Methods: Crosssectional analytic study in a stratified random sample of 169 adolescents who were in third to fifth grades of high school. Reynolds Adolescent Depression Scale (RADS) was applied to measure dependent variable and other questionnaires were applied for associated factors. Results: 18,9% of the students presented depression; family dysfunction was observed in 75,7%; 68% presented distorted body image; 18,9% showed bullying; 5,7% of the men and 22,4% of the women evidenced depression. The following associated factors presented a meaningful connection with depression: family dysfunction (p=0,037), distorted body image (p=0,020) and gender (p=0,028). Conclusions: This study showed that an important percentage of adolescents suffer depression. The most outstanding associated factors were distorted body image and family dysfunction. No significant relationship between depression and bullying was found.